Upper-extremity musculoskeletal disorders: how many cases can be prevented? Estimates from the COSALI cohort - Nambiema, Aboubakari; Bodin, Julie; Fouquet, Natacha; Bertrais, Sandrine; Stock, Susan; Aublet-Cuvelier, Agnès; Descatha, Alexis; Evanoff, Bradley; Roquelaure, Yves (Scandinavian Journal of Work, Environment & Health, 2020)
' ' OBJECTIVE ': 'This study aimed to estimate the proportion and number of incident upper-extremity musculoskeletal disorders (UEMSD) cases attributable to occupational risk factors in a working population. ' ' METHODS ': 'Between 2002−2005, occupational physicians randomly selected 3710 workers, aged 20–59, from the Pays de la Loire (PdL) region. All participants underwent a standardized clinical examination. Between 2007−2010, 1611 workers were re-examined. This study included 1246 workers who were free of six main clinically diagnosed UEMSD at baseline but were diagnosed with at least one of these UEMSD at follow-up [59% of men, mean age: 38 (standard deviation 8.6) years]. Relative risks and population-attributable fractions (PAF) were calculated using Cox multivariable models with equal follow-up time and robust variance. The total number of incident UEMSD in the PdL region was estimated after adjustment of the sample weights using 2007 census data. The estimated number of potentially avoidable UEMSD was calculated by multiplying PAF by the total number of incident UEMSD in PdL. ' ' RESULTS ': 'At follow-up, 139 new cases of UEMSD (11% of the study sample) were diagnosed. This represented an estimated 129 320 incident cases in the PdL in 2007. Following adjustment for personal factors, 26 381 (20.4% of all incident UEMSD) were attributable to high physical exertion, 16 682 (12.9%) to low social support, and 8535 (6.6%) to working with arms above shoulder level. ' ' CONCLUSIONS ': 'A large number and important proportion of incident UEMSD may be preventable by reducing work exposures to physical exertion and working with arms above shoulder level as well as improving social support from co-workers/supervisors.
Keywords: cohort study; COSALI; france; MSD; musculoskeletal disease; musculoskeletal disorder; occupational risk factor; physical exertion; preventable case; prevention; upper-extremity musculoskeletal disorder